(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
In this article, issues related to financing the needs of the population for social support from the state budget funds have been highlighted and analyzed. Also, attention has been paid to optimizing the costs of social support in the composition of state budget expenditures.